Pendampingan Kepala Sekolah Dan Guru SD Pada Lokakarya Kurikulum 2 Projek Penguatan “Profil Pelajar Pancasila” Tahun Kedua Di Kabupaten Soppeng - Hamzah, Rahma Ashari (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2023)
The project to strengthen the profile of Pancasila students is essential because it can provide a deeper understanding of what strengthening Pancasila values is like for students in schools that apply the independent curriculum. The purpose of implementing the assistance is to strengthen further the knowledge of school principals and teachers regarding the implementation of projects to strengthen Pancasila student profiles and to design ideas for modifying project modules that are by the context of the situation and needs of the school. The method in mentoring workshop 2 was a participatory learning committee, namely the principal and 2 teacher representatives for each school, which consisted of 4 levels of elementary school, namely SD Negeri 5 Mattiropole. SD Negeri 238 Laempa, SD Negeri 118 Ujung, and SD Negeri 100 Dare Bunga-Bungae, which are in the Soppeng Regency area, were held on December 10, 2022, by involving participants directly during the activity. The final result of the curriculum 2 workshop activities is in the form of product design ideas for project modifications to strengthen the profile of Pancasila students. Thus, project assistance to strengthen Pancasila student profiles can positively impact schools in the Mobilizing School Program, strengthening various skills, competencies, and characters from curricular activities in schools.